2013
DOI: 10.1038/srep01162
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-assisted thermostability engineering of a soluble T cell receptor using phage display

Abstract: We here report a novel phage display selection strategy enabling fast and easy selection of thermostabilized proteins. The approach is illustrated with stabilization of an aggregation-prone soluble single chain T cell receptor (scTCR) characteristic of the murine MOPC315 myeloma model. Random mutation scTCR phage libraries were prepared in E. coli over-expressing the periplasmic chaperone FkpA, and such over-expression during library preparation proved crucial for successful downstream selection. The thermosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 54 publications
0
35
0
Order By: Relevance
“…To elucidate the intrinsic pMHC binding properties of the TCRs 364 and 380, we first expressed and purified both TCRs in a single-chain TCR (scTCR) format containing stabilizing mutations (P50 TRAV , L50 TRBV , F103 TRBV , and P2 linker ) (13,14). We then performed surface plasmon resonance (SPR) studies employing recombinant, soluble TCRs and pMHCs.…”
Section: Generation Of α-Gliadin-specific T Cell Clones and Tcr Clonimentioning
confidence: 99%
“…To elucidate the intrinsic pMHC binding properties of the TCRs 364 and 380, we first expressed and purified both TCRs in a single-chain TCR (scTCR) format containing stabilizing mutations (P50 TRAV , L50 TRBV , F103 TRBV , and P2 linker ) (13,14). We then performed surface plasmon resonance (SPR) studies employing recombinant, soluble TCRs and pMHCs.…”
Section: Generation Of α-Gliadin-specific T Cell Clones and Tcr Clonimentioning
confidence: 99%
“…In contrast, the pIII-derived clone, 57AE06 (using IGHV3) was expressed extremely well, but bound poorly to the antigen, indicating selection largely based on favorable expression characteristics. Although expression and stability are closely connected4647, it did not appear to be the case with this clone. This was even more pronounced for the other pIII clone, which had a high thermal stability, but was expressed at very low level.…”
Section: Discussionmentioning
confidence: 71%
“…We thought it likely that some periplasmic factor must be assisting LacZ folding. Because previous studies have implicated the periplasmic chaperones skp and fkpA in the folding of heterologous proteins (23)(24)(25)(26)(27)(28)(29), we chose to see what effect disruption of these genes might have on the ␤-galactosidase activity of a strain expressing the malF-lacZ102 fusion in the absence of DsbA. While disruption of skp did not decrease ␤-galactosidase activity, we found that disruption of fkpA reduced it by a factor of 2.6 (Fig.…”
Section: Resultsmentioning
confidence: 97%